KAJIAN EKSISTENSI NILAI-NILAI DAN MAKNA MOTIF KERAJINAN KAIN TENUN TRADISIONAL ETNIS KULISUSU - La Ode Monto Bauto; Sulisvia; Jamiluddin; Dewi Anggraini (Universitas Halu Oleo (UHO), 2023)
The purpose of this research is to (1) To analyze the process of making Kulisusu ethnic woven fabrics (2) To analyze the meaning of the motifs contained in the traditional woven crafts of the Kulisusu ethnic (3) To analyze the zzeducational values ​​contained in the traditional weaving crafts of the Kulisusu ethnic. This research includes qualitative research and uses a type of descriptive approach, data collection is done by using the method of observation, interviews, documentation. The results showed that the process of making Kulisusu ethnic woven fabric crafts consisted of 9 stages, namely 1) materials; 2) tools 3) traditional rituals 4) drawing motifs: 5) spinning threads; 6) sorting yarn (pouluri); 7) Arranging yarn (Lopo); 8) tying the motifs on the warp; 9) weave (Mohoru). The meaning of the motif contained in the woven fabric of the Kulisusu ethnicity is that the vertical motif means the relationship between humans and the creator; horizontal motives that are meaningful about human relationships with other humans; and natural motifs that are meaningful about the relationship between humans and nature.The educational values ​​contained in the traditional weaving crafts of the Kulisusu ethnicity are religious values, honest values, love for the motherland and social care values ​​and responsibility values.